2005
DOI: 10.1002/j.1556-6678.2005.tb00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Creating Mentoring Relationships Between Female Faculty and Students in Counselor Education: Guidelines for Potential Mentees and Mentors

Abstract: Mentoring can support all aspects of women's professional (and often personal) lives as students, educators, researchers, practitioners, and leaders in the counseling profession. So that female mentors and mentees know what to expect from each other, the authors draw upon the mentoring literature and their own experiences in mentoring relationships to provide guidelines for mentoring relationships by defining the means and ends that can be used to establish and maintain woman-to-woman professional mentoring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Although a number of researchers have examined the usefulness and benefits of mentoring in higher education and, specifically, in counselor education (Arthur, & Russell-Mayhew, 2010;Briggs & Pehrsson, 2008;Buyukgoze-Kavas, Taylor, Neimeyer, & Guneri, 2010;Casto, Caldwell, & Salazar, 2005;Farrell, 2007;Taylor & Neimeyer, 2009;Walker, 2006), few researchers have studied the mentoring relationship and the impact of the mentor's engagement in dual, or multiple roles, through the use of the Mentoring Functions Scale. Thus, the purpose of our study was to examine the relationship between perceived dual roles of the mentor and the impact on the mentoring relationship.…”
Section: Purpose and Rationale Of The Studymentioning
confidence: 99%
“…Although a number of researchers have examined the usefulness and benefits of mentoring in higher education and, specifically, in counselor education (Arthur, & Russell-Mayhew, 2010;Briggs & Pehrsson, 2008;Buyukgoze-Kavas, Taylor, Neimeyer, & Guneri, 2010;Casto, Caldwell, & Salazar, 2005;Farrell, 2007;Taylor & Neimeyer, 2009;Walker, 2006), few researchers have studied the mentoring relationship and the impact of the mentor's engagement in dual, or multiple roles, through the use of the Mentoring Functions Scale. Thus, the purpose of our study was to examine the relationship between perceived dual roles of the mentor and the impact on the mentoring relationship.…”
Section: Purpose and Rationale Of The Studymentioning
confidence: 99%
“…Packard et al (2004) suggested that women in particular have benefited from mentoring and that female faculty who mentor female doctoral students in counselor education programs can offer experiences to the students that are unique and invaluable to their personal and professional development. Women can offer women a forum to listen, provide feedback, and challenge their female students without the influence of gender bias and in a supportive environment (Casto, Caldwell, & Salazar, 2005;Greene, 2002).…”
Section: Women Mentoring Womenmentioning
confidence: 99%
“…Mentoring relationships offer social work educators a chance to give back to the profession when they nurture novice professionals (Casto, Caldwell, & Salazar, 2005). Allen-Meares (2006) refers to mentoring as a process for her to "transfer the lessons I have learned to the next generation" (p. 19).…”
Section: Background Literature Mentoring Relationshipsmentioning
confidence: 99%